2013
DOI: 10.3390/toxins5030488
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Pea-Associated F. proliferatum and F. verticillioides Populations Revealed by FUM1 Sequence Analysis and Fumonisin Biosynthesis

Abstract: Fusarium proliferatum and F. verticillioides are considered as minor pathogens of pea (Pisum sativum L.). Both species can survive in seed material without visible disease symptoms, but still contaminating it with fumonisins. Two populations of pea-derived F. proliferatum and F. verticillioides strains were subjected to FUM1 sequence divergence analysis, forming a distinct group when compared to the collection strains originating from different host species. Furthermore, the mycotoxigenic abilities of those st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 41 publications
5
36
0
Order By: Relevance
“…It is known to be the main cause of maize cob fusariosis (along with Fusarium verticillioides), but can also colonize wheat, barley, rice, asparagus, garlic, pea, onion, tomato, pineapple, fig and various palms (Jurado et al, 2010;Kerényi et al, 2002;Stępień et al, 2011b;von Bargen et al, 2009;Waśkiewicz et al, 2013). Moreover, it has been isolated from uncultivated plants including reed, sorrel, prairie grasses and pine (Bhale et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…It is known to be the main cause of maize cob fusariosis (along with Fusarium verticillioides), but can also colonize wheat, barley, rice, asparagus, garlic, pea, onion, tomato, pineapple, fig and various palms (Jurado et al, 2010;Kerényi et al, 2002;Stępień et al, 2011b;von Bargen et al, 2009;Waśkiewicz et al, 2013). Moreover, it has been isolated from uncultivated plants including reed, sorrel, prairie grasses and pine (Bhale et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Though mycotoxin analyses were not planned for this study, they definitely would contribute to knowledge in the field (some analyses have already been performed and more extensive research is planned on this material). In fact, significant amounts of fumonisins have been found in the seeds of cultivars Eureka and Turnia (35). Taking our results into account, it can be concluded that some pea-originating Fusarium strains can be regarded as specific for the host, although results have also shown that susceptibility of individual pea cultivars to pathogenic fungi vary.…”
Section: Discussionmentioning
confidence: 70%
“…Water availability and temperature at specific plant growth stage are particularly crucial for disease development and severity. Woudenberg et al (25) indicated that fungi can infect different parts of a plant at various isolated from the same plant host (33,35). Moreover, analysis of FUM1 sequence can be used to evaluate the contamination with fumonisins; however, significant intraspecific differences in mycotoxigenic abilities have been reported (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Fusarium species are able to generate mycotoxins (moniliformin -MON and fumonisins -FBs), which pose potential health hazards to humans and animals [9][10][11]. The most abundant fumonisin produced in nature is fumonisin B 1 (FB 1 ), a suspected risk factor for esophageal and liver cancers, neural tube defects, and cardiovascular problems [12][13][14][15] in populations where food contains contaminated maize.…”
Section: Introductionmentioning
confidence: 99%